Sayyid Qutb's Interpretations: A Focus on Political Concepts - Muhammad Yusry Affandy bin Md Isa; Muhammad Syahmi bin Shakhruddin (Universiti Sains Islam Malaysia, 2024)
Maʿālim Al-Qurʾān Wa Al-Sunnah, Volume 20 Issue 1 Page (45-64)